Un semillero de controversias: La epopeya de Artigas de Zorrilla de San Martín - Zubillaga, Carlos (Revista Complutense de Historia de América, 2008)
A polysemic text La Epopeya de Artigas (first edition 1910), reelaborated throughout one decade of deep social and political changes in Uruguay, showed some historiographical conceptions that tried to overcome pure and harmless erudition and the dryness of positivism, ignited the polemic, forcing his author to polemize with writers from different backgrounds and with different intentions.